A globally distributed Syndiniales parasite dominates the Southern Ocean micro-eukaryote community near the sea-ice edge - Clarke, LJ; Bestley, S; Bissett, A; Deagle, BE (The ISME Journal, 2018)
Syndiniales (Dinophyceae, Alveolata) are a diverse parasitic group common in all marine environments, but their ecological role remains poorly understood. Here we show an unprecedented dominance of a single Syndiniales group I operational taxonomic unit (OTU) across 3000 km of Southern Ocean transects near the sea-ice edge. This super-abundant OTU consistently represented >20%, and in some locations >50%, of eukaryote 18S rDNA sequences. Identical 18S V4 sequences have been isolated from seven Northern Hemisphere locations, and the OTUs putative V9 rDNA sequence was detected at every station of the global Tara Oceans voyage. Although Syndiniales taxa display some host specificity, our identification of candidate Southern Ocean hosts suggests this OTU associates with distinct phyla in different parts of the world. Our results indicate Syndiniales are key players in surface waters near the vast and dynamic sea-ice edge in the worlds most biologically productive ocean.